PENGARUH BUDAYA ORGANISASI DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA PT SCOREX TEKNOLOGI INDONESIA DIVISI KONSULTAN MARKETING JAKARTA SELATAN - Arman Maulana; Dodi Prasada (Journal of Research and Publication Innovation, 2025)
This study aims to analyze the effect of organizational culture and work stress on employee performance at PT Scorex Teknologi Indonesia. The study uses a quantitative approach with a population of 70 employees. The sampling method used is saturated sampling, where the entire population is used as the sample. The results show that organizational culture (X1) has a positive and significant effect on employee performance (Y). The regression coefficient obtained is 0.741, with a t-value of 7.999, which is higher than the t-table value of 1.995, and the significance value is less than 0.05 (0.000 < 0.05). Additionally, work stress (X2) also has a positive and significant effect on employee performance in a partial manner, with a regression coefficient of 0.345. The t-value of 3.694 is greater than the t-table value of 1.996, and the significance value is less than 0.05 (0.000 < 0.05). Simultaneously, both organizational culture and work stress have a positive and significant effect on employee performance. The F-value of 38.263 is greater than the F-table value of 3.13, with a significance level of 0.000 (0.000 < 0.05). The coefficient of determination (R²) of 0.533 indicates that 53.3% of the variation in employee performance can be explained by organizational culture and work stress, while the remaining 46.7% is influenced by other factors not studied. Based on the results of this study, it can be concluded that both organizational culture and work stress have a positive and significant effect on employee performance, both individually and together, at PT Scorex Teknologi Indonesia